Suyûtî’s Approach to The Khabarî Attributes -in The Context of at-Tawshîh - Agitoğlu, Nurullah (Fırat University, 2014)
Khabari attributes, a sub topic of divine attributes which are located at the center of the issues of Kalam, are those attributes mentioned in the verses and hadiths as God?s hand and face, God?s coming down, being close etc. There have been different approaches towards the explanations of the attributes. The Salafi?s approach is to accept the khabarî attributes which are mentioned in the Qur?an and the hadith without ta?wîl interpretation and without making any further comments. This approach has been called as tafwîz or tawakuf. Muhaddithun?s approach to the subject has been generally parallel with the opinion of Salafî?s. This article studies asSuyûtî?s approach to some khabarî attributes, who was a prominent figure in the cultural history of Islam, which will be examined in the context of his ta?lik work at-Tawshîh Ala al-Câmii asSahîh li al-Buhârî which is a sharh commentary on Bukharî?s al-Câmiu as-Sahîh. As-Suyûtî?s approach to the khabarî attributes will be sought to be determined and evaluated from the point of view of his explanations and comments about khabarî attributes in his work.

Kelam ilmindeki konuların odağında yer alan ilahî sıfatlar içinde bulunan haberî sıfatlar; Allah'ın eli, yüzü, gözü, gelmesi, inmesi ve yakın olması gibi hususlarla ilgili âyet ve hadislerde geçen sıfatlardır. Âlimler arasında bu sıfatlara yönelik farklı yaklaşımlar olmuştur. Bu yaklaşımlar içinde selefin yaklaşımı, Kur?ân?da ve hadislerde geçen haberî sıfatlara iman edip, te?vîl etmeden, herhangi bir yoruma gitmemektir. Buna tefvîz veya tevakkuf metodu da denmiştir. Hadisçilerin konuya yaklaşımı genelde selefin görüşüne paralel olmuştur. Bu çalışmada da bir hadisçi olarak, İslâm kültür tarihinde önemli bir şahsiyet olan Suyûtî?nin bazı haberî sıfatlara yaklaşımı, Buhârî?nin el-Câmiü?s-Sahîh?i üzerine yaptığı ve aslında bir ta?lik çalışması olan et-Tevşîh Ale?lCâmii?s-Sahîh Li?l-Buhârî isimli eseri çerçevesinde ele alınacaktır. Suyûtî?nin, eserinde ele aldığı haberî sıfatlar ile ilgili yaptığı veya aktardığı açıklama ve yorumlar çerçevesinde, bu sıfatlara yaklaşımı tespit edilmeye ve değerlendirilmeye çalışılacaktır.
BİR HADÎSÇİ OLARAK SUYÛTÎ’NİN BAZI HABERÎ SIFATLARA YAKLAŞIMI -et-Tevşîh Adlı Eseri Bağlamında-